If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + -54 = 2 + -9 Reorder the terms: -54 + t = 2 + -9 Combine like terms: 2 + -9 = -7 -54 + t = -7 Solving -54 + t = -7 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + t = -7 + 54 Combine like terms: -54 + 54 = 0 0 + t = -7 + 54 t = -7 + 54 Combine like terms: -7 + 54 = 47 t = 47 Simplifying t = 47
| 4x^2+4x=-36 | | 3x=21+12 | | 2x-5=34 | | 8x=600 | | 2x=5y-10 | | 2-11=12-d | | 5x+3(x-5)=6x+2x-15 | | 5x+160=70 | | 600x=8 | | 4.5=10x | | 5a+4(3am-8)=4+13a | | 5x+33=123 | | -7(-1x+9)=-126 | | -4x-46=18 | | 17z+10=39 | | n-335=21n-5 | | x^5-49x^3=0 | | 2h+1=6 | | 5+y=6(5+0.1) | | 25d+0.45m=40d+0.25m | | 10x^3-8x^2-18x= | | -9-2x=-41 | | 15b+24c+33= | | 1000x=3 | | 2(6x+4)+2=4(x+1) | | 3c-2(3c-4)=4-5(2c-3) | | 5+5p=1p | | 9(3x-16)+15=6x-24 | | 4-3(6n-3)=95 | | 65+15x= | | 20x=500 | | -4u(u-5)(u-4)=0 |